Buddhahood and Metanoia: Buddhist-Christian Dialogue in Korea - Kang-nam (Journal of Dharma, 1995)
Buddhism and Christianity are currently the two most dominant religions in South Korea, with approximately one half of the country's population of 44.5 million as their adherents. Among these, about one half are Buddhists and the other half are Christians. I Under such circumstances, it is not difficult for anybody to see that the dialogical and cooperative 'relationship between these two religions in Korea should be a prerequisite or even an imperative for the peaceful and harmonious future of Korean society. The purpose of this paper is 1) to have a brief survey of the historical background of these two religions in Korea. 2) to analyze the present situation of Buddhist-Christian relationship in Korea, and 3) to explore the questions as to what would be the desirable direction for these two religions to head for in their future encounters. It will be argued that Korean Buddhism and Christianity, realizing what important historical and religious functions they can perform in Korean society, should ' work together" and "think together" for the socloethical welfare and spiritual well-being of Korean people.